PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSET, WORKING CAPITAL TURNOVER TERHADAP PERTUMBUHAN LABA (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2014 - 2018) - Matry Desi; Dicky Arisudhana (Jurnal Akuntansi dan Keuangan, 2020)
Earnings growth is the company's ability to see the ups and downs of profits each year, which will give effect to the survival of the company and can influence the decisions of investors and potential investors who will invest their capital into the company. The purpose of this study was to determine the effect of the current ratio, debt to equity ratio, return on assets, and working capital turnover on profit growth. This study uses secondary data with a population of 10 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange with 10 companies in 2014-2018. The sampling technique used was purposive sampling with multiple linear regression analysis methods. The results of this study indicate that there is no influence between the current ratio, debt to equity ratio, and working capital turnover on earnings growth, while there is an influence between return on assets on earnings growth.